Elite perceptions of poverty and inequality - Moore, Mick; Reis, Elisa Pereira (London Zed Books Ltd, 2005)
Drawing on case studies from a range of developing countries, the contributors to this volume discover major differences in how national elites understand and represent poverty. The classic threats that induced elites in late 19th century Europe, such as the fear of crime, epidemics, military weakness or political unrest--do not feature prominently in the consciousness of most developing country elites. Nor do most of them believe that there is a viable solution to poverty through public action. The findings help to explain the relative ineffectiveness of poverty reduction strategies so far, and illustrate the need to present poverty in ways that tie in with how national elites understand their world.--Publisher description.
Introduction: Elites, Perceptions and Poverties--Elisa Reis and Mick Moore * Perceptions of Poverty and Inequality among Brazilian Elites--Elisa Reis * Voices from the Top of the Pile: Elite Perceptions of Poverty and the Poor in the Philippines--Gerard Clarke & Marites Sison * So Near and Yet So Far: Elites and Imagined Poverty in Bangladesh--Naomi Hossain and Mick Moore * Haitian Elites and Their Perceptions of Poverty and Inequality--Omar Ribeiro Thomaz * Elite Perceptions of Poverty and Poor People in South Africa--Noushin Kalati and James Manor * Elite Perceptions of the Poor: Reflections on a Comparative Research Project --Abram de Swaan * Elites, Poverty and Public Policy: From Structure to Strategy--Mick Moore and Naomi Hossain.
Includes bibliographical references and index.
Keywords: Poverty -- Developing countries -- Case studies; Elite (Social sciences) -- Developing countries -- Attitudes -- Case studies